G585(P) Structured proforma – A solution to accurate documentation OF neonatal resuscitation? – An experience. (27th April 2016) - Yip, MQ; Sultan, K; Nayak, S; Penumala, VV; Arumugam, J Mahalingam; Mukherjee, S; Momoh-Ojewuyi, A
Abstract : Context: Often the details of neonatal resuscitation are not accurately documented, causing difficulty to understand what exactly happened on retrospect. Problem: The standard of documentation of neonatal resuscitation in our unit was not up to standards. Repeated prompts and requests to the team members didnt improve the quality. Assessment of problem and analysis of its causes: Following a serious case review, it was identified that the details of resuscitation obtained fro the documentation didn't reflect the true events. This had medico-legal implications as well as there was an inquest. Intervention: A structured proforma was conceived to cover the important aspects of a neonatal resuscitation. Study design: We retrospectively collected details of resuscitation documentation from the electronic medical records of 42 randomly selected neonates. 21 of them were born during February 2014–August 2014, in the period where no proforma was in use, while the other 21 were born during August 2014–December 2014, a period after the introduction of proforma. Strategy for change: We identified the target user group which consisted of a multi-disciplinary team of neonatal doctors, neonatal nurses and members of midwifery team. all the stakeholders from the different staff teams were formally introduced and trained on using the proforma. A formal start date was agreed for the trial. The team was instructed to document the details as per the proforma. The proforma was made readily available in print format in all possible neonatal resuscitation areas. Copies of proforma were also stocked in the resuscitation trolleys and resuscitation bags. Measurement of improvement: Data was collected and compared from all categories from before and after the use of proforma. Results are as follows, Documentation of type of bleep call, time of bleep, names of neonatal staff attending improved by 71%, 48%, and 57% respectively. Documenting Apgar scores improved by 38%. Documentation of details of respiratory support improved from 15–71% to 85–100%. Documentation of time of first gasp and first breath were almost 0% before proforma, increased by 58% and 63% respectively. Documentation of use of resuscitation drugs improved from 67% to 100%. No significant difference noted in documentation of intubation details. The percentage of documentation doubled for transportation details. Documentation of resuscitation outcome improved from 0% to 86%. Documentation of parental communication improved from 19% to 75%. (Please see graphs below) Effects of changes: Improved quality of documentation has enabled better understanding of events in the resuscitation for the whole team. This has made the team to have effective communication with the parents/families later. We had informal feedback from the users that in day to day practice and in a stressful situation such as neonatal resuscitation, the structured proforma was very useful. Lessons learnt: Improving documentation is always difficult. introducing the proforma made a big difference. We think the prompting nature of the proforma has enabled the users to document the vital details of resuscitation Message for others: We recommend that all neonatal resuscitation should be documented on a structured proforma. Following the above results, the proforma is now in regular use in our unit.